1987
DOI: 10.1007/bf00190532
|View full text |Cite
|
Sign up to set email alerts
|

A direct enzyme-linked immunosorbent assay (ELISA) for antibodies to enterobacterial Re core glycolipid and lipid A

Abstract: We have developed an ELISA for IgM and IgG antibodies to the core glycolipid (CGL) of the Re mutant Salmonella minnesota R 595, and to lipid A. Anti-CGL antibodies have been detected in sera from 37% of healthy blood donors, whereas anti-lipid A activities were found in 13% of individuals only. The anti-CGL and anti-lipid A activities were examined in patients in a surgical intensive care unit, selected on the basis of a definite risk of infectious complications due to Gram-negative bacteria. Of the patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…In this study, we used different ELISAs and an immunoprecipitation procedure to detect the LPS-precipitable antibodies in a sample of the Belgian blood donor population, with the aim of preparing effective immune globulin with high and consistent levels of functional antibodies. In agreement with other reports [35][36][37][38][39][40], we found a natural occurrence of antibodies to LPS, core glycolipid and lipid A in normal subjects. The presence of antibodies to antigenic determinants of various LPSs was expected.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we used different ELISAs and an immunoprecipitation procedure to detect the LPS-precipitable antibodies in a sample of the Belgian blood donor population, with the aim of preparing effective immune globulin with high and consistent levels of functional antibodies. In agreement with other reports [35][36][37][38][39][40], we found a natural occurrence of antibodies to LPS, core glycolipid and lipid A in normal subjects. The presence of antibodies to antigenic determinants of various LPSs was expected.…”
Section: Discussionsupporting
confidence: 93%
“…Other authors have observed that naturally occurring antibody to LPS is present in most individuals to a variable degree [38][39][40]. A response may be boosted by infections but also by vaccination [39,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of endogenous anti-LPS antibodies (IgG and/or IgM) to the panel of smooth LPS, rough LPS, and lipid A antigens was evaluated by a direct enzyme-linked immunosorbent assay (ELISA) as previously described with minor modi®cations (Nys et al 1987;Camus et al 1997). All samples were assayed, and were screened using twofold dilutions of individual preparations from 1:100 to 1:51200 in contact buer and negative controls (uncoated wells).…”
Section: General Proceduresmentioning
confidence: 99%
“…The presence of endogenous anti-LPS antibodies (IgG) to the panel of smooth LPSs, rough LPSs, and lipid A antigens was measured by a direct ELISA, as previously described with minor modifications [25]. Briefly, the plates (Nunc) were coated either with a mixture of the 13 smooth (S)-form LPSs (10 &ml of each), with a mixture of the nine rough (R)-form LPSs (10 pg/ml of each), or with individual purified smooth or rough LPSs at a concentration of 10 pg/ml and lipid A at a concentration of 5 pg/ml.…”
Section: Anti-lps Antibody Assaymentioning
confidence: 99%